Long-term exposure to residential ambient fine and coarse particulate matter and incident hypertension in post-menopausal women. (August 2017) - Honda, Trenton; Eliot, Melissa N.; Eaton, Charles B.; Whitsel, Eric; Stewart, James D.; Mu, Lina; Suh, Helen; Szpiro, Adam; Kaufman, Joel D.; Vedal, Sverre; Wellenius, Gregory A.
Abstract: Background: Long-term exposure to ambient particulate matter (PM) has been previously linked with higher risk of cardiovascular events. This association may be mediated, at least partly, by increasing the risk of incident hypertension, a key determinant of cardiovascular risk. However, whether long-term exposure to PM is associated with incident hypertension remains unclear. Methods: Using national geostatistical models incorporating geographic covariates and spatial smoothing, we estimated annual average concentrations of residential fine (PM2.5 ), respirable (PM10 ), and course (PM10–2.5 ) fractions of particulate matter among 44, 255 post-menopausal women free of hypertension enrolled in the Women's Health Initiative (WHI) clinical trials. We used time-varying Cox proportional hazards models to evaluate the association between long-term average residential pollutant concentrations and incident hypertension, adjusting for potential confounding by sociodemographic factors, medical history, neighborhood socioeconomic measures, WHI study clinical site, clinical trial, and randomization arm. Results: During 298, 383 person-years of follow-up, 14, 511 participants developed incident hypertension. The adjusted hazard ratios per interquartile range (IQR) increase in PM2.5, PM10, and PM10–2.5 were 1.13 (95% CI: 1.08, 1.17), 1.06 (1.03, 1.10), and 1.01 (95% CI: 0.97, 1.04), respectively. Statistically significant concentration-response relationships were identified for PM2.5 and PM10 fractions. The association between PM2.5 and hypertension was more pronounced among non-white participants and those residing in the Northeastern United States. Conclusions: In this cohort of post-menopausal women, ambient fine and respirable particulate matter exposures were associated with higher incidence rates of hypertension. These results suggest that particulate matter may be an important modifiable risk factor for hypertension. Highlights: Long-term air pollution exposures were associated with higher incidence rates of hypertension in post-menopausal women. Associations between PM2.5 and hypertension were stronger among non-white participants and those living in the Northeast. These results suggest that particulate matter may be an important modifiable risk factor for hypertension.